2009
DOI: 10.5551/jat.e598
|View full text |Cite
|
Sign up to set email alerts
|

Remnant Lipoproteins As Strong Key Particles to Atherogenesis

Abstract: Recent epidemiologic studies have revealed that hypertriglyceridemia is associated with atherosclerosis independent of other coronary risk factors. However, it is difficult to select patients at high risk for coronary artery disease using only serum triglyceride levels compared with low-density lipoprotein cholesterol levels since multiple factors are associated with elevating triglycerides. Atherosclerotic diseases with high triglyceride levels can be found in patients with familial combined hyperlipidemia, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 77 publications
1
115
0
Order By: Relevance
“…The atherogenic effects of RLPs on the endothelium include upregulation of proinflammatory cytokines, monocyte recruitment and activation, and increased production of prothrombotic factors 4. Changes in RLPs in the postprandial state may lead to endothelial dysfunction as measured by flow‐mediated dilation 40.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The atherogenic effects of RLPs on the endothelium include upregulation of proinflammatory cytokines, monocyte recruitment and activation, and increased production of prothrombotic factors 4. Changes in RLPs in the postprandial state may lead to endothelial dysfunction as measured by flow‐mediated dilation 40.…”
Section: Discussionmentioning
confidence: 99%
“…Though not as well recognized as LDL particles for their role in atherogenesis, RLPs have several proatherogenic properties, including proinflammatory and prothrombotic effects; in addition, resident macrophages scavenge and retain RLPs in the subendothelial space 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Increased triglyceride-rich lipoproteins, such as chylomicron and VLDL, are hydrolyzed to remnant particles (Merkel 2009). Recent studies have focused on these remnant lipoproteins as atherogenic particles, showing that remnant lipoproteins can penetrate the endothelial wall and remain in the subendothelial space (Fujioka & Ishikawa 2009). Remnant lipoproteins have also been reported to be associated with inflammation, endothelial dysfunction, foam cell formation, and vascular smooth muscle cell proliferation (Fujioka & Ishikawa 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on these remnant lipoproteins as atherogenic particles, showing that remnant lipoproteins can penetrate the endothelial wall and remain in the subendothelial space (Fujioka & Ishikawa 2009). Remnant lipoproteins have also been reported to be associated with inflammation, endothelial dysfunction, foam cell formation, and vascular smooth muscle cell proliferation (Fujioka & Ishikawa 2009). Several studies have reported that the level of remnant-like particle cholesterol (RLP-C) is increased in diabetic patients (Taniguchi et al 2000, Schaefer et al 2002 and is associated with an increased risk of cardiovascular disease (Fukushima et al 2001(Fukushima et al , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Many basic studies have suggested that accumulated CMR particles may promote atherogenicity in the arterial wall. Indeed, elevated intestinally derived remnant lipoproteins have been associated with an increased risk for cardiovascular diseases 25,26) . CM and CMR have a characteristic apolipoprotein B-48 (apoB-48), each having one apoB-48 molecule per particle.…”
Section: Laboratory Measurementsmentioning
confidence: 99%